Multiple Identities Management - Natasza Kosakowska-Berezecka (Frontiers Research Topics, 2018)
In this ebook, a collection of 18 papers presents empirical research, as well as novel theoretical considerations, on how multiple identities are being managed by the individuals holding them. The papers draw on theories from social psychology in the context of the social identity approach. The first chapter presents eight papers on different types of multiple identity configurations in a variety of contexts, and the costs and benefits of these configurations for the individual (e.g., well-being). The second chapter gives insights on how conflict between multiple identities is managed by individuals. And the final chapter analyses how multiple identities impact intragroup and intergroup relations.